Characterization of amorphous hydrogenated chlorinated plasma polymers - Rossi, Diego [UNESP]; Schreiner, Wido H.; Durrant, Steven F. [UNESP] (My University, 2016)
Thin films were produced by plasma enhanced chemical vapor deposition from propanol-chloroform-argon mixtures. The main system parameter studied was the percentage of chloroform in the chamber feed, CCl. Plasma polymers doped with chlorine were produced at deposition rates of up to 110 nm min-1. As revealed by infrared- and X-ray photoelectron spectroscopy, the films consisted of a hydrogenated carbon matrix with a carbon content of at least 80 at.%, and a roughly constant oxygen content of about 12 at.%. A maximum chlorine content of ~8 at.% was obtained. The surface contact angle of the films was around 75°, and was reduced slightly at greater chlorine contents. Optical properties were obtained from ultraviolet-visible-near infrared spectroscopic data. While the refractive index of the films was around 1.56 independently of CCl, the chlorinated films showed a distinct optical gap of ~2.5 eV compared to ~1.9 eV for the unchlorinated film.
Keywords: Chlorinated films; PECVD; Plasma polymers; Tauc gap